2014
DOI: 10.1002/oby.20658
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weight loss on ankle‐brachial index and interartery blood pressures

Abstract: Objective To assess whether weight loss improves markers of peripheral artery disease and vascular stenosis. Design and Methods The Action for Health in Diabetes randomized clinical trial compared intensive lifestyle intervention (ILI) for weight loss to a control condition of diabetes support and education (DSE) in overweight or obese adults with type 2 diabetes. Annual ankle and brachial blood pressures over four years were used compute ankle-brachial indices (ABIs) and to assess inter-artery blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…As a measure of differences in systolic blood pressure measures among arteries, we calculated the maximum inter-artery differences in systolic blood pressure among the four ankle arterial sites (Espeland et al, 2014a), which we will refer to as MIAD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a measure of differences in systolic blood pressure measures among arteries, we calculated the maximum inter-artery differences in systolic blood pressure among the four ankle arterial sites (Espeland et al, 2014a), which we will refer to as MIAD.…”
Section: Methodsmentioning
confidence: 99%
“…If such an association is evident, it may signal that approaches to slowing or preventing declines in ABI may be promising strategies for preserving cognitive function. Secondly, there is growing evidence that other differences in systolic pressures among arterial sites, beyond what is captured by ABI, may also be markers of atherosclerosis (Kimura et al, 2004; Clark et al, 2007; Verberk et al, 2011; Espeland et al, 2014a). ABI evaluations include systolic blood pressure measurements taken from four ankle arterial sites (right and left dorsal pedis and posterior tibial arteries): we are the first to explore whether differences among these measures, and changes in such differences over four years, also serve as independent risk factors for cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Weight reduction improves endothelial function [280] and lowers CRP [281], oxLDL [282], cIMT [283], wave reflections and arterial stiffness [284], especially when combined with exercise [285e287], but does not influence ABI values [288]. Endurance exercise leads to improved central haemodynamics [289] and endothelial function [290]; the effect of high-intensity resistance training on arterial stiffness is detrimental [290].…”
Section: Pharmacological Modification Of Vascular Biomarkers and CV Riskmentioning
confidence: 99%
“…Previous study suggested that high sIAD might represent hemodynamic differences caused by ongoing endothelial dysfunction and arterial stiffness [12]. Obesity and abdominal obesity are associated with the risk of cardiovascular disease directly or indirectly related to hypertension, hyperglycemia, and lipid metabolism disorders [28,29], and are consistent risk factors of metabolic syndrome that is an independent predictor of arterial stiffness and endothelial dysfunction [30][31][32][33].…”
Section: V Discussionmentioning
confidence: 99%